Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

given $ax^2y''+bxy'+cy=0$ a,b, and c are real. x is positive. I want to show that  $$a \frac{d^2y}{dv^2} +(b-a)\frac{dy}{dv} +cy =0.$$ This is a problem in a elementary text, I have found a more rigours method online, but I'm trying to make sense of the last step in my own less rigours idea. 

Using the coefficients $a$, $b$, and $c$, I observe that if this is true then $$xy'=\frac{dy}{dv}\quad\text{and}\quad x^2y''= \frac{d^2y}{dv^2} - \frac{dy}{dv},$$ so if I show the two statements above are true I will have justified the subsitution.

Let $\ln x = v$ $$\frac{1}{x} = \frac{dv}{dx}$$ $\ln$ is one to one so it has an inverse and  $$\begin{align*} x &= \frac{dx}{dv}\\ xy'&= \frac{dx}{dv} \frac{dy}{dx}\&&\text{by the chain rule}\\ xy'&= \frac{dy}{dv}. \end{align*}$$ Great one down one to go. Continuing with the above... $$x \frac{dy}{dx} = \frac{dy}{dv}.$$ I take the derivative with respect to $x$ of both sides, using the product rule on the right. $$x \frac{d^2y}{dx^2} + \frac{dy}{dx} = \frac{d}{dx}  \left( \frac{dy}{dv} \right)$$ I dont feel so good about the right side, but I keep going anyway.

$$x \frac{d^2y}{dx^2} = \frac{d}{dx}  \left( \frac{dy}{dv} \right) - \frac{dy}{dx}$$ since $x$ is $e^v$, $x$ is its own derivative with respect to $v$. I multiply through by $x$: $$x^2 \frac{d^2y}{dx^2} = x \frac{d}{dx}  \left( \frac{dy}{dv} \right) - \frac{dy}{dx} \frac{dv}{dx}$$ chain rule on the far right.

$$x^2 \frac{d^2y}{dx^2} = x \frac{d}{dx}  \left( \frac{dy}{dv} \right) - \frac{dy}{dv}$$ I'm so close but I'm stuck! all I want to say is: $$x^2y''= \frac{d^2y}{dv^2} - \frac{dy}{dv}$$ and it is very sugestive to write: $$x^2 \frac{d^2y}{dx^2} = \frac{dx}{dv} \frac{d}{dx}  \left( \frac{dy}{dv} \right) - \frac{dy}{dv}$$ but what could it mean to cross out the $dx/dx$? that is in my way? as I was told before here such operations are "dubious" though I'm still trying to grasp why.

But I know this is true so it must be the case that for these functions $$\frac{dx}{dv} \frac{d}{dx}  \left( \frac{dy}{dv} \right) = \frac{d^2y}{dv^2}$$ perhaps I can say that the kind of functions that work in the above are just the kind I'm working with and then I would be done? 

share|improve this question
    
Is the original equation $ax^2y''+bxy'+cy=0$? I think you dropped an $x$ in the second term. –  Raskolnikov Jun 23 '11 at 20:22
    
What happened to my shorter version? –  Noteventhetutorknows Jun 23 '11 at 20:24
    
Yes, I dropped an x. –  Noteventhetutorknows Jun 23 '11 at 20:25
1  
The last step is just the chain rule again. –  Raskolnikov Jun 23 '11 at 20:25
2  
@Not: I believe what Raskolnikov is saying: If $f = \frac{dy}{dv}$ then $\frac{df}{dx} = \frac{df}{dv} \times \frac{dv}{dx}$. So with $f = \frac{dy}{dv}$ we get $\frac{d^2y}{dv^2} \times \frac{dv}{dx}$. –  Aryabhata Jun 23 '11 at 20:50

1 Answer 1

Start with $$a{x^2}y'' + bxy' + cy = 0$$

which is an Euler-Cauchy DE of second degree. Now make the change of variables,

$$x = e^z$$

From here you get that

$$dx = e^z dz$$

So now you have

$$\frac{{dy}}{{dx}} = \frac{{dy}}{{dz}}\frac{{dz}}{{dx}}=\frac{{dy}}{{dz}}\frac{1}{x}$$

Thus

$$bx\frac{{dy}}{{dx}} = b\frac{{dy}}{{dz}}$$

Which is what you correctly derived.

For the second equality go this way

$$\eqalign{ & x = {e^z} \cr & \frac{{dy}}{{dx}} = {e^{ - z}}\frac{{dy}}{{dz}} \cr & \frac{{{d^2}y}}{{d{x^2}}} = \frac{d}{{dx}}\left( {{e^{ - z}}\frac{{dy}}{{dz}}} \right) \cr & \frac{{{d^2}y}}{{d{x^2}}} = \frac{d}{{dz}}\left( {{e^{ - z}}\frac{{dy}}{{dz}}} \right)\frac{{dz}}{{dx}} \cr & \frac{{{d^2}y}}{{d{x^2}}} = \left( {{e^{ - z}}\frac{{{d^2}y}}{{d{z^2}}} - {e^{ - z}}\frac{{dy}}{{dz}}} \right)\frac{{dz}}{{dx}} \cr & \frac{{{d^2}y}}{{d{x^2}}} = {e^{ - 2z}}\left( {\frac{{{d^2}y}}{{d{z^2}}} - \frac{{dy}}{{dz}}} \right) \cr & {x^2}\frac{{{d^2}y}}{{d{x^2}}} = \frac{{{d^2}y}}{{d{z^2}}} - \frac{{dy}}{{dz}} \cr} $$

Notice that what is used is the chain rule, in a rather "algebraic" way.

You can prove by induction that

$${x^n}{D^n}y = \mathcal{D}\left( {\mathcal{D} - 1} \right) \cdots \left( {\mathcal{D} - n + 1} \right)y$$

Where $\mathcal{D}=\dfrac{d}{dz}$ and $D = \dfrac{d}{dx}$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.